A comparison of test methodologies to enable the improved understanding of soccer boot traction - Clarke, J. D.; Carre, M. J.; Kirk, R. F. (The Engineering of sport 7, Volume 1, 2008)
The difficulties of mechanically representing actual human movements have long been recognised. However, repeatable mechanical tests are necessary to quantify the characteristics of footwear-surface interactions. Improving understanding of the interactions between footwear and surfaces can advise athletes on the Optimum choice of footwear in order to balance their athletic performance with injury risk. Many mechanical test devices have been developed to measure traction, generally simulating the movement of a shoe over a sports surface. Current velocity controlled devices measure the peak traction that occurs during a movement. However, high-speed video analysis suggests the peak traction does not represent an athlete losing performance when slipping. A force controlled traction rig has recently been developed to examine a different approach. This rig measures the initial resistance to movement, when the surface first fails. Load cells in the horizontal and vertical directions measure the resistance to movement of a loaded studded plate allowing different interaction mechanisms to be studied. A comparison between the methodologies used in the traction testing of sport surfaces is discussed. Results from velocitycontrolled and force-controlled rigs are presented and the virtues of each method compared.